Pengaruh Kondisi Sosial Ekonomi Terhadap Kesehatan Mental Mahasiswa Perantau Di UIN Syarif Hidayatullah Jakarta - Nasichah N; Nova Aprilia Maulani; Artika Elfarianti; Muhammad Febriansyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study is motivated by the increasing prevalence of mental health issues among migrant students who must adapt to a new environment while coping with economic pressures during their studies. Unstable socioeconomic conditions are suspected to influence the levels of stress, anxiety, and psychological well-being of migrant students at UIN Syarif Hidayatullah Jakarta. This study aims to examine the influence of socioeconomic conditions on the mental health of migrant students. The research employs a qualitative approach, with data collected through in-depth interviews with migrant students as the primary data source. The collected data were analyzed using descriptive analysis to understand students' experiences, economic challenges, and their impact on psychological well-being. The findings indicate that socioeconomic conditions have a significant influence on the mental health of migrant students. Students experiencing financial constraints tend to face higher levels of psychological distress, including academic stress, anxiety, and difficulties in meeting their daily living needs. In addition, limited social support and high academic demands further exacerbate their mental health conditions. Conversely, students who receive adequate financial and social support are generally better able to adapt and maintain emotional stability.